A characterization of the uniform convergence points set of some convergent sequence of functions - (:unkn) unknown (De Gruyter, 2021)
We characterize the uniform convergence points set of a pointwisely convergent sequence of real-valued functions defined on a perfectly normal space. We prove that if $X$ is a perfectly normal space which can be covered by a disjoint sequence of dense subsets and $A\subseteq X$, then $A$ is the set of points of the uniform convergence for some convergent sequence $(f_n)_{n\in\omega}$ of functions $f_n:X\to \mathbb R$ if and only if $A$ is $G_\delta$-set which contains all isolated points of $X$. This result generalizes a theorem of J\'{a}n Bors\'{i}k published in 2019.
Keywords: set of points of uniform convergence; uniformly Cauchy sequence